Sosialisasi dan Praktik Islamic Parenting di Era Digital bagi Orang Tua Murid Yayasan Ponpes Darussaadah, Nganjuk - Anik Indramawan; Nur Fuad; Leily Vidya Rahma; Agus Tohawi; Mastur Mastur; Muhamad Ali Anwar (Eastasouth Journal of Effective Community Services, 2025)
This community service program focused on the socialization and practical application of Islamic parenting in the digital era for parents of students at the Darussaadah Islamic Boarding School Foundation, Nganjuk. The initiative aimed to equip parents with knowledge and skills to address the challenges of raising children amidst rapid technological advancements and pervasive digital influences. Activities included interactive seminars, discussions, and hands-on workshops emphasizing the integration of Islamic values with effective digital-age parenting strategies. The results demonstrated increased parental awareness of the importance of monitoring children’s digital activities, fostering discipline, and instilling strong moral and religious foundations. Parents reported improved confidence in guiding their children to use technology responsibly while upholding Islamic principles. The program highlights the necessity of continuous education and collaboration between parents and educators to ensure children’s holistic development in the digital age. This approach serves as a model for strengthening family resilience and character education within Islamic communities.